Comparative transcriptomic analysis of the gene expression and underlying molecular mechanism of submergence stress response in orchardgrass roots - Qu, Minghao; Zheng, Yuqian; Bi, Lei; Yang, Xingyun; Shang, Panpan; Zhou, Xiaoli; Zeng, Bing; Shen, Bingna; Li, Wenwen; Fan, Yan; Zeng, Bing (Frontiers in Plant Science, 2023)
Submergence stress creates a hypoxic environment. Roots are the first plant organ to face these low-oxygen conditions, which causes damage and affects the plant growth and yield. Orchardgrass (Dactylis glomerata L.) is one of the most important cold-season forage grasses globally. However, their submergence stress-induced gene expression and the underlying molecular mechanisms of orchardgrass roots are still unknown. Using the submergence-tolerant ‘Dianbei’ and submergence-sensitive ‘Anba’, the transcriptomic analysis of orchardgrass roots at different time points of submergence stress (0 h, 8 h, and 24 h) was performed, generating 118.82 Gb clean data. As compared with the control, a total of 6663 and 9857 differentially expressed genes (DEGs) were detected in Dianbei, while 7894 and 11215 DEGs were detected in Anba at 8 h and 24 h post-submergence-stress, respectively. Gene Ontology (GO) enrichment analysis obtained 986 terms, while Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis obtained 123 pathways. Among them, the DEGs in plant hormones, mitogen-activated protein kinase (MAPK) and Ca2+ signal transduction were significantly differentially expressed in Dianbei, but not in Anba. This study was the first to molecularly elucidate the submergence stress tolerance in the roots of two orchardgrass cultivars. These findings not only enhanced our understanding of the orchardgrass submergence tolerance, but also provided a theoretical basis for the cultivation of submergence-tolerant forage varieties.